APLIKASI SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT PADA CV. RAJAWALI CITRA MANDIRI - Suwandi S.E., M.M. (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
Rajawali Citra Mandiri is a moving company in the furniture field located at Jl. Ciremai Raya Blok D12 Perumnas, Cirebon - West Java. CV. Rajawali Citra Mandiri is currently facing problems in processing data on credit sales and inventory, because it still uses transaction recording manually so that in terms of security and accuracy is less guaranteed. This study aims to facilitate the management of CV. Rajawali Citra Mandiri in processing data on credit sales and inventory. Making this application using PHP and MySQL. The research process is carried out by searching for data by observation and interviews. The stage of making this application is the analysis of the weaknesses of the old system, data search, design, manufacture, testing, and implementation of credit sales information systems with PHP and MySQL. The final results of the application that have been made in the form of goods reports and credit sales reports, which contain credit sales transaction data and overall expenditure. The research method used in this research is a descriptive method with case studies, the steps taken are observation and interviews. To input the required data, an analysis and design of the system is then performed using the Flowchart, Context Diagram, DFD, and ERD tools. The programming language is PHP Hypertext Preprocessor while the database uses localhost. The results of this study are an accounting information system for cash receipts for credit sales consisting of functions to handle procedures such as credit sales procedures, installment payment procedures, procedures for making reports on the realization of credit sales, procedures for receiving cash from installment payments, and recording procedures accounting. Keywords: Information Systems, Credit Sales, PHP, MySQL.